Psychological Well-Being dan Readiness For Change Pada Karyawan - Diah Sastaviana; Ria Sakinah Waji (LPPM Universitas Abdurrab, 2025)
This study aims to analyze the relationship between psychological well-being and readiness for change among employees across various sectors of companies and organizations. A quantitative research method was employed, utilizing the Psychological Well-Being Scale and the Readiness for Change Scale as measurement instruments. The sample was obtained using incidental sampling, consisting of 119 employees from diverse companies and organizations in Makassar City. Data were analyzed using simple linear regression. The analysis revealed a strong and significant relationship between psychological well-being and readiness for change, r(117) = .79, p < .001. The coefficient of determination (R²) = .62 indicated that psychological well-being contributed 62% to readiness for change. This contribution is considered relatively high, suggesting that employees with higher levels of psychological well-being are more likely to demonstrate greater readiness for change.